The Story Of Chicken Licken - Ormerod, Jan (Walker, 1999)
Reading Together is a learn-to-read series of picture books for young children and parents to enjoy together. There are four levels each consisting of six books offering a variety of reading experiences: stories poems rhymes and songs traditional tales and information books.
Keywords: Fairy Tales & Folklore; Folklore & Mythology; General; Readers (Elementary); Social Science; Juvenile Fiction